Konstribusi Strategi Coping Terhadap Homesickness Pada Mahasiswa Baru Yang Merantau Di Perguruan Tinggi Kota Bukittinggi - Wiriawan, Larasati; Primanita, Rida Yanna (EDU SOCIATA ( JURNAL PENDIDIKAN SOSIOLOGI ), 2024)
The purpose of this study is to see if there are differences in coping strategies in dealing with homesickness in new students who migrate in Bukittinggi city colleges. In this study using correlational quantitative methods. The sample in this study consisted of 97 new students who migrated. The sampling technique used in this study was purposive sampling with participant criteria a) Students of class 2023 who migrated in the city of Bukittinggi b) Aged 18-22 years c) Migrants from outside the West Sumatra region. The scale used in this study with homesickness variables was compiled by researchers who referred to aspects put forward by Stroebe (2002), and coping strategy variables were compiled by researchers who referred to aspects put forward by Lazarus & Folkman (1984). Based on the analysis obtained with the value of t count = -125,865 with a significance of 0.000. So it can be concluded that there are differences in coping strategies in dealing with homesickness in new students who migrate in Bukittinggi city colleges.